2016
DOI: 10.9734/bjmmr/2016/26873
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ketamine Spraying on the Postoperative Sore Throat and Hoarseness after Tracheal Intubation

Abstract: Aims: Sore throat, hoarseness, and cough are postoperative complications caused by tracheal intubation in general anesthesia. The aim of this study was to investigate the role of preoperative ketamine splashing on reducing postoperative sore throat. Study Design: A cross-sectional/ randomized, double-blinded clinicall study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(11 citation statements)
references
References 18 publications
0
11
0
Order By: Relevance
“…In all, 30 including 2278 participants provided data on the incidence of sore throat at 24 hours after surgery/extubation . Topical application of ketamine was associated with a reduced incidence of postoperative sore throat compared to non‐analgesic methods (159/1161 vs 384/1117; RR, 0.45; 95% CI, 0.37‐0.54; P < .001; I 2 = 23.0%; Figure ).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…In all, 30 including 2278 participants provided data on the incidence of sore throat at 24 hours after surgery/extubation . Topical application of ketamine was associated with a reduced incidence of postoperative sore throat compared to non‐analgesic methods (159/1161 vs 384/1117; RR, 0.45; 95% CI, 0.37‐0.54; P < .001; I 2 = 23.0%; Figure ).…”
Section: Resultsmentioning
confidence: 99%
“…In all, 15 studies reported that there were no systemic or local adverse events . One study reported that there were no differences in adverse events between topical ketamine and non‐analgesic methods . Another study reported that there were no psychomimetic effects related to ketamine…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations